Pengaruh Program Homeschooling Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Pesantren Nurul Syarofa Bogor - Muhit, Abdul; Wardani, Rizky akmal (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This study aims to determine the Learning Motivation of homeschooled students. This study uses a quantitative approach with analytical observational research using a cross-sectional approach, while the data collection techniques used are observation, documentation and questionnaires. For data analysis, the researcher uses correlational analysis. The research subjects were taken from the criteria determined by the researcher, namely the subjects were students who attended the homeschooling program at the Nurul Syarofa Islamic Boarding School in Bogor and were willing to be research subjects. The results of the study showed that in accordance with Law No. 20/2003 on the National Education System "Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state". The results of the study showed that 30 student samples or 100.0% of them were not motivated to learn Islamic Religious Education in the homeschooling program. There is a significant relationship between two variables that have an impact on student motivation according to the results of statistical tests where the probability value is 0.015